Projeto de um sistema de aferições de baixo custo para parâmetros termodinâmicos de uma bancada dinamométrica - Monteiro, Caio César Pantaleão (2021)
This work presents the development of a low-cost gauging system, based on Arduino and some sensors, for thermodynamic parameters of a dynamometric bench. Important properties of internal combustion engines, such as performance tests and analyses, and a historical perspective regarding their current use are highlighted, as environmental concerns about the sustainable use of resources have increased considerably. The experimental dynamometric system consists of an internal combustion engine coupled to elements that allow the verification of torque and power to the brake. Through the projected system, in addition to its feasibility and construction, the aim is to verify the possibility of measuring the specific consumption of fuel and of carrying out energy and exergy balances.